Global Neoconservative Turn - Vuletić, Vladimir M. (Sociološki pregled, 2019)
The text advocates the thesis that neoconservatism is a global response and not the cause of the crisis of the contemporary world capitalist system. Theoretical foundations are established for the thesis that neoconservatism always appears when capitalism is in danger, while the 2008 crisis represented only the tip of an iceberg warning the gravity of the structural crisis of capitalism. In that respect, neoconservatism is an ideological/political attempt to preserve existing relations in the world capitalist system, disturbed by the accelerated globalization process.
Keywords: neoconservatism; neoliberalism; populism; capitalism